Evolution of the dynamic properties of concrete in a sulfate environment. (10th June 2020) - Liu, Peng; Chen, Ying; Yu, Zhiwu; Lu, Zhaohui; Shi, Weihua
Highlights: Effect of sulfate attack on dynamic properties of concrete was investigated. A novel method of sloving damping ratio of concrete was proposed. Damping ratio of concrete deduced by different forms is different. Waveform attenuation coefficient increases with increase of solution concentration. Wave curve of vibration in concrete is represented by cosine function. Abstract: The effects of sulfate solution concentrations, erosion form, and erosion age on the dynamic properties of concrete were investigated. A novel methodology for determining the damping ratio of concrete was proposed based on the enveloping curve of the waveform amplitude. Moreover, variations in the dynamic properties of concrete attacked by sulfate were analysed. The results indicated that the sulfate solution concentration, erosion form, and erosion age had significant effects on the dynamic properties of concrete. With an increase in the sulfate solution concentration, the dynamic elasticity modulus of concrete first increased and then decreased, until it finally stabilized. Although the change trends in the relative dynamic elasticity modulus of concrete specimens with different strengths attacked by sulfate were similar, the corresponding degree of variation decreased with an increase in the strength of the concrete. With the partial immersion form in which the sulfate attacked, the dynamic elasticity modulus of the concrete increased with an increasing sulfate solution concentration but decreased with an increase in the concrete strength. The vibration of waves in concrete gradually decayed until it disappeared, and the wave curve could be represented by a cosine function. The damping ratio of concrete was deduced from the different forms of segmented time or the difference in the accumulations of initial time, which was caused by varying decay rates. The attenuation coefficient of the waveform in concrete increased with an increase in the sulfate solution concentration and erosion age and decreased with an increase in the concrete strength.